Dietary composition and its associations with insulin sensitivity and insulin secretion in youth. Issue 3 (14th February 2014) - Henderson, Mélanie; Benedetti, Andrea; Gray-Donald, Katherine
<x content-type="archive" xml:space="preserve">Abstract</x> The objectives of the present study were to examine the associations between macronutrient intake and insulin sensitivity (IS) and insulin secretion (ISct), taking into consideration moderate-to-vigorous physical activity (MVPA), fitness and sedentary behaviour. Caucasian youth (n 630) aged 8–10 years at recruitment, with at least one obese biological parent, were studied (QUebec Adipose and Lifestyle InvesTigation in Youth cohort). IS was measured using the homeostasis model assessment (HOMA) of insulin resistance and Matsuda IS index. ISct was measured using HOMA2 %-β, the ratio of the AUC of insulin:glucose over the first 30 min (AUC I/Gt= 30min) of the oral glucose tolerance test and AUC I/Gt= 120min over 2 h. Fitness was measured using VO2peak, percentage of fat mass by dual-energy X-ray absorptiometry, and 7 d MVPA using accelerometry; screen time (ST) by average daily hours of self-reported television, video game or computer use. Dietary composition was measured using three non-consecutive dietary recalls. Non-parametric smoothing splines were used to model non-linear associations; all models were adjusted for age, sex, season, pubertal stage, MVPA, fitness, ST and adiposity. The percentage of total daily energy from dietary protein, fat, saturated fat and carbohydrate and the consumption of dietary vitamin D, sugar-sweetened beverages, fibre and portions of fruits and vegetables were taken into consideration. No dietary component was associated with any measure of IS after adjusting for MVPA, fitness, ST and adiposity. For every 1 % increase in daily protein intake (%), AUC I/Gt= 30min decreased by 1·1 % (P= 0·033). Otherwise, dietary composition was not associated with ISct. While long-term excess of energy intake has been shown to lead to overweight and obesity, dietary macronutrient composition is not independently correlated with IS or ISct in youth.